2023
DOI: 10.3389/fpsyg.2023.1138282
|View full text |Cite
|
Sign up to set email alerts
|

Dual mediating effects of social support and fertility stress on mindfulness and fertility quality of life in infertile men: A case-control study

Abstract: BackgroundInfertility is one of the three major public health problems in the world, bringing immense physical and psychological damage to men and affecting the quality of men’s fertility life. Thus, the purpose of this study was to analyze the status of social support, fertility stress, mindfulness, and fertility quality of life in infertile men, and to explore the dual mediating effects of social support and fertility stress on mindfulness and fertility quality.MethodsA case–control group study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…Job stress was also found to have a negative effect on quality of life and partially negative effects on job satisfaction. These results indicate that job stress not only decreases job satisfaction but also lowers the quality of life, supporting previous studies that have shown various negative effects of job stress (Abulizi et al, 2023;Kong et al, 2020;Min, 2014;Vinothkumar et al, 2016).…”
Section: Theoretical Contributionsupporting
confidence: 90%
See 1 more Smart Citation
“…Job stress was also found to have a negative effect on quality of life and partially negative effects on job satisfaction. These results indicate that job stress not only decreases job satisfaction but also lowers the quality of life, supporting previous studies that have shown various negative effects of job stress (Abulizi et al, 2023;Kong et al, 2020;Min, 2014;Vinothkumar et al, 2016).…”
Section: Theoretical Contributionsupporting
confidence: 90%
“…Mindfulness was found to have a positive effect on job satisfaction and quality of life, supporting previous research that suggests regular attention and focus through mindfulness can enhance job satisfaction and quality of life (Abulizi et al, 2023; Choi & Koh, 2015; Fortney et al, 2013). Job satisfaction was found to have a very high positive effect on quality of life, supporting previous research (Kong et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“… 15 Previous studies have overlooked the interactions and differences between the quality of life in the context of infertility between spouses. 17 In reality, partners’ perceptions of fertility issues have a cross-partner impact on the patients’ emotional, physical, and relational quality of life. 34 A better quality of life for women was predicted by a better partner’s ability to identify and describe emotions, as well as by a better quality of life for men, who were more externally oriented thinking than their spouses.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Prior studies have ignored the interactions and differences between spouses’ QoL and patients’ QoL. 17 Studies on women or men alone could not fully understand the important role played by their spouses. Therefore, it is necessary to further explore the interactive effects that the stress experienced by both patients and their spouses may have on each other’s QoL.…”
Section: Introductionmentioning
confidence: 99%